Group Editorial for the Special Issue on Cooperatives and Alternative Food Systems Initiatives Working Together to Build Cooperative Food Systems - Anderson, Colin Ray; Brushett, Lynda; Gray, Thomas; Renting, Henk (Journal of Agriculture, Food Systems, and Community Development, 2014)
First paragraphs: The combined challenges of food insecurity, agriculture-related environmental decline, corporate concentration, and the decline of community resilience are being met by growing societal interest in developing more just and sustainable food systems. A recent emphasis on cooperation and innovative forms of collective action within the food movement invokes a community-centered approach to food provisioning where collective problem-solving and democracy take center place in the development agenda (Ikerd, 2012). Cooperative alternative food networks are becoming powerful tools for community development and important vehicles for cultivating democratically controlled food systems at multiple scales. The papers in this special issue provide an important contribution to our understanding of the function, the challenges, and the potential of collective action in enabling more just and resilient food systems. Cooperative alternative food networks represent a break from the competitive productivism of the dominant food economy and create new relational spaces that hold promise for overcoming the pragmatic and political limits of some of the more individualistic approaches in the local/ sustainable food movement. These include cooperative forms of: food hubs, local food networks, farmers' markets, CSAs, box schemes, buying clubs, and value chains, along with a range of agriculture and food cooperatives owned by farmers, consumers, workers, and in emerging multistakeholder cooperative structures. With a renewed emphasis on civic governance, the resulting food-provisioning systems are based on principles of participatory democracy, solidarity, and reciprocity (Renting, Schermer, & Rossi, 2012) and provide spaces to nurture collective subjectivities required for transformative food practice and politics (Levkoe, 2011)....